2012
DOI: 10.1074/mcp.m112.017251
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-wide Analysis of Lysine Acetylation Suggests its Broad Regulatory Scope in Saccharomyces cerevisiae

Abstract: Post-translational modification of proteins by lysine acetylation plays important regulatory roles in living cells. The budding yeast Saccharomyces cerevisiae is a widely used unicellular eukaryotic model organism in biomedical research. S. cerevisiae contains several evolutionary conserved lysine acetyltransferases and deacetylases. However, only a few dozen acetylation sites in S. cerevisiae are known, presenting a major obstacle for further understanding the regulatory roles of acetylation in this organism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
241
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(253 citation statements)
references
References 82 publications
11
241
1
Order By: Relevance
“…Seven of the 11 acetylated Lys residues are highly conserved between species and were also shown to be Lys acetylated in yeast, rat, mouse, and human tissue, respectively (Supplemental Fig. S5; Choudhary et al, 2009;Weinert et al, 2011;Henriksen et al, 2012;Lundby et al, 2012;Sol et al, 2012). Furthermore we detected a 1.6-to 2-fold increase in Lys acetylation of the AAC carriers in the srt2 mutants (Fig.…”
Section: The Aac Carriers As Well As the Atp Synthase Complexes Are Tmentioning
confidence: 52%
“…Seven of the 11 acetylated Lys residues are highly conserved between species and were also shown to be Lys acetylated in yeast, rat, mouse, and human tissue, respectively (Supplemental Fig. S5; Choudhary et al, 2009;Weinert et al, 2011;Henriksen et al, 2012;Lundby et al, 2012;Sol et al, 2012). Furthermore we detected a 1.6-to 2-fold increase in Lys acetylation of the AAC carriers in the srt2 mutants (Fig.…”
Section: The Aac Carriers As Well As the Atp Synthase Complexes Are Tmentioning
confidence: 52%
“…An earlier study examining global acetylation in yeast identified a similar number of sites (4208) (12). Surprisingly, only 21% of the total acetylation sites identified in these two studies were found in both data sets (supplemental Fig.…”
Section: Fig 7 Ada2 Selectively Regulates Gcn5-dependent Acetylationsmentioning
confidence: 87%
“…Although recent efforts have demonstrated that acetylation is a frequent post-translational modification, little is known about the regulation of most of these marks (12)(13)(14)(15). Moreover, although recruitment to chromatin is seen as the key step in acetylation of histone tails, little is known about the mechanism behind non-histone substrate selection.…”
mentioning
confidence: 99%
“…6C), suggesting that the coupling between carbohydrate storage and aging (38) is mediated in part by acetylation of the PKA at a conserved residue. Although significant, the effects measured with both mammalian and yeast mutants are small, suggesting that other acetylation sites reported in both the regulatory and catalytic subunits (34)(35)(36) or other indirect mechanisms may contribute to PKA regulation. …”
Section: Filteau Et Almentioning
confidence: 98%
“…S5). Five residues are acetylated in Bcy1 (34,35), and at least two of them are conserved and acetylated in mammals (Fig. 5A) (36).…”
Section: Filteau Et Almentioning
confidence: 99%